Endocrine‐disrupting potentials of equine estrogens equilin, equilenin, and their metabolites, in the medaka Oryzias latipes: in silico and DNA microarray studies. Issue 9 (22nd January 2015) - Uchida, Masaya; Ishibashi, Hiroshi; Yamamoto, Ryoko; Koyanagi, Akiko; Kusano, Teruhiko; Tominaga, Nobuaki; Ishibashi, Yasuhiro; Arizono, Koji
ABSTRACT: Although several previous studies have demonstrated the presence of equine estrogens in the aquatic environment, limited data are currently available on the endocrine‐disrupting potentials in fish and the risks they pose to aquatic organisms. To investigate the interactions of major equine estrogens equilin (Eq) and equilenin (Eqn), as well as their metabolites 17α‐dihydroequilin, 17β‐dihydroequilin, 17α‐dihydroequilenin and 17β‐dihydroequilenin, with the estrogen receptor α (ERα) of medaka ( Oryzias latipes ), a three‐dimensional model of the ligand‐binding domain (LBD) of ERα was built in silico, and docking simulations were performed. The docking simulation analysis indicated that the interaction of 17β‐dihydroequilenin with the ERα LBD is the most potent, followed by those of 17α‐dihydroequilin and 17β‐dihydroequilin, whereas those of Eq and Eqn were least potent. We further analyzed gene expression profiles in the livers of male medaka exposed to Eq and Eqn. A DNA microarray representing 6000 genes revealed that 24‐h exposure to Eq and Eqn (100 ng/L) upregulated the expression of 6 and 34 genes in the livers of males, respectively. Genes upregulated by Eq included the estrogenic biomarker genes vitellogenins and choriogenins, suggesting the estrogenic potential of Eq. In contrast, Eqn exposure upregulated several cancer‐related genes, such as mediator complex subunit 16 and RAS oncogene family members, suggesting a carcinogenic potential for Eqn. These results suggest that equine estrogens may have not only endocrine‐disrupting potentials via the ERα signaling pathway but also carcinogenic potency in male medaka. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Although several previous studies have demonstrated the presence of equine estrogens in the aquatic environment, limited data are currently available on the endocrine‐disrupting potentials in fish and the risks they pose to aquatic organisms. To investigate the interactions of major equine estrogens equilin (Eq) and equilenin (Eqn), as well as their metabolites 17α‐dihydroequilin, 17β‐dihydroequilin, 17α‐dihydroequilenin and 17β‐dihydroequilenin, with the estrogen receptor α (ERα) of medaka ( Oryzias latipes ), a three‐dimensional model of the ligand‐binding domain (LBD) of ERα was built in silico, and docking simulations were performed.